Value-For-Money Audit for Accountability and Performance Management in Local Government in Ghana. Issue 7 (7th June 2017) - Bawole, Justice Nyigmah; Ibrahim, Mohammed
ABSTRACT: Public sector organizations, including local government (LG) entities, continue to resort to value for money (VFM) audit to enhance performance and accountability. Based on the analysis of the consolidated reports on the annual performance-based Functional Organizational Assessment Tool (FOAT)—VFM audit—in Ghana to determine the efficacy of VFM on performance, this article argues that VFM audits constitute a significant public management tool that could enhance LG performance. However, the FOAT reports, like most VFM audits, only provide quantitative evidence, which fails to capture the qualitative or other relevant explanatory factors behind the recorded performance improvement.